The development of science comic to improve student’s understanding in elementary school - Ika Maryani; Luluk Amalia (Jurnal Inovasi Pendidikan IPA, 2018)
This study aims to: (1) understand the steps of science comic development for grade V elementary school students, (2) understand the feasibility of comic science from learning aspect, materials aspect, and instructional media aspect, (3) understand the effectiveness of science comics to increase students understanding in elementary school. This is a research and development by using ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Product validation tests are carried out by material experts, learning experts, media experts, teacher response, and students respond. Product implementation is conducted on the grade V students of Muhammadiyah Ngijon 1 elementary school. Data collection is used questionnaire and test. The results showed that the assessment from media experts is 81.25 (high feasibility); from the science, material expert is 85.00 (high feasibility); from learning experts is 93.18 (high feasibility). Teachers and students in the small group obtained a value of 97.50 (high feasibility) and in large group trials obtained a value of 94.58 (high feasibility). The effectiveness of science comic is tested by  Wilcoxon signed test and the result of Z value at -3.903 on the asimp significance of 0.000 on two-tailed test. The tets result show that the significance value is smaller than alpha (0.05); then it can be concluded that "Ho is rejected and Ha accepted". It means that there are differences in students' understanding of pre-test and post-test in science learning, so it can be concluded that science comis is effective to improve the understanding